Exploring Within-Discipline Variation of Lexical Bundle Use: An Example from Medical Research Articles and Medical Case Reports - Ndeye Bineta Mbodj; Viviana Cortes (Revista Brasileira de Linguística Aplicada)
Abstract: Studies that focus on the use of formulaic language in academic writing primarily investigated the use of different types of formulaic sequences in academic research articles in various disciplines. These studies revealed dramatic variations in the use of formulaic language across academic disciplines (e.g., Cortes, 2004; Hyland, 2008; Jalali; Moini, 2014; Shahriari, 2017). However, there is evidence that discipline alone may not be enough to determine linguistic variation (Gray, 2015), as different registers within one discipline may reflect different linguistic characteristics depending on specific communicative purposes (Biber; Conrad, 2019). In the case of medical written discourse, different medical registers may call for the use of different formulas to convey different communicative intents. This is the case of the medical research article (MRA) and the medical case report (MCR). In this study, we will focus on the identification and analysis of lexical bundles in medical discourse, particularly in MRAs and MCRs. Lexical bundles (Biber et al., 1999) are groups of three or more words that frequently occur in a given register. They are identified empirically, using specially designed computer programs that run through the texts in a language corpus and flag expressions of three or more words that repeat frequently, employing a strictly corpus-driven approach (Cortes, 2015). Using specially designed software, lexical bundles of 3+ words were identified in each corpus. These expressions were later analyzed according to their structure and the functions they performed to conduct a comparison across the two registers using taxonomies adapted from the literature (Biber; Conrad; Cortes, 2004; Hyland, 2008).